Smart Mirror: A Journey to the new world - Jha, Pratibha; Jha, Prashant; Khan, Mufeed; Mittal, Kajol (International Journal of Computer Sciences and Engineering, 2019)
A Smart Mirror is the most recent in innovative home stylistic theme and in the market. In view of the client studies and model execution, we present the improvement of an enhancing machine that fuses intelligent administrations of data, offered through a UI on the surface of a mirror. Our work depends on the possibility that we as a whole take a gander at the mirror when we go out, so for what reason wouldn't the mirror end up smart. It is a custom mirror establishment that is both a mirror and a display. It takes information from the web including time, climate, stock reports, quotes and more to stay up with the latest. The smart mirrors, which continue to work today and will take place in future technology, provide users with both mirror and computer-assisted information services to the user. These systems can be connected to the Web, and the information in certain locations on the mirror may transmit data. In the smart mirror system performed in the working scope, using the Raspberry Pi 3 micro-controller card, the weather, time and location information taken from the Web services, the activity calendar information of the user, the phone rings information and the camera image is included. Some enhancements can be controlled via the microphone in the smart mirror, with the help of the voice commands.